2002
DOI: 10.1128/iai.70.8.4336-4343.2002
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Cytokines Enhance the Interaction of Mannheimia haemolytica Leukotoxin with Bovine Peripheral Blood Neutrophils In Vitro

Abstract: Mannheimia (Pasteurella) haemolytica A1 is the primary bacterial agent of bovine pneumonic pasteurellosis (shipping fever), which is characterized by acute lobar fibronecrotizing pneumonia with extensive peripheral blood neutrophil (PMN) infiltration in small airways and alveoli (4,39,47). Several virulence factors of M. haemolytica play an important role in the pathogenesis of pasteurellosis (7, 13). Foremost among these is a leukotoxin (LKT), whose effects are specific for ruminant leukocytes and platelets (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 45 publications
1
35
0
3
Order By: Relevance
“…It is likely that well documented LFA-1 specific mechanisms including membrane raft formation [34], and cytokine mediated "insideout" signaling may also play a role in mediating LktA-induced biological effects. A recent report has in fact indirectly addressed this question and demonstrated that exposure of bovine neutrophils to IL-1ß, TNF-α and IFN-γ increased the expression of LFA-1 leading to enhanced LktA effects [29]. These and other reports demonstrating that diverse ligands capable of eliciting intracellular signals that enhance LFA-1 mediated LktA-effects [29][30][31] suggest that LFA-1 affinity and avidity changes occurring through "inside-out" signaling may affect overall LktA biological effects on the target cell.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is likely that well documented LFA-1 specific mechanisms including membrane raft formation [34], and cytokine mediated "insideout" signaling may also play a role in mediating LktA-induced biological effects. A recent report has in fact indirectly addressed this question and demonstrated that exposure of bovine neutrophils to IL-1ß, TNF-α and IFN-γ increased the expression of LFA-1 leading to enhanced LktA effects [29]. These and other reports demonstrating that diverse ligands capable of eliciting intracellular signals that enhance LFA-1 mediated LktA-effects [29][30][31] suggest that LFA-1 affinity and avidity changes occurring through "inside-out" signaling may affect overall LktA biological effects on the target cell.…”
Section: Discussionmentioning
confidence: 99%
“…A recent report has in fact indirectly addressed this question and demonstrated that exposure of bovine neutrophils to IL-1ß, TNF-α and IFN-γ increased the expression of LFA-1 leading to enhanced LktA effects [29]. These and other reports demonstrating that diverse ligands capable of eliciting intracellular signals that enhance LFA-1 mediated LktA-effects [29][30][31] suggest that LFA-1 affinity and avidity changes occurring through "inside-out" signaling may affect overall LktA biological effects on the target cell. It is very likely that binding of LktA to the I-domain of the CD11a subunit may confer, through allosteric interaction, a conformation to the CD18 subunit that is compatible for LktA signaling.…”
Section: Discussionmentioning
confidence: 99%
“…The latter is known to decrease host defence amongst others by diminishing the activities of T lymphocytes, B lymphocytes, monocytes and macrophages [24,67] and by interfering with the host's antigen presentation machinery to evade the host's immune response in vivo [74,134]. Moreover, it has been shown that leukocyte exposure to inflammatory cytokines released in response to BHV-1 infection (interleukin-1 beta, interleukin-8, tumour necrosis factor alpha and interferon gamma) can modulate the migration and functional activation of bovine leukocytes [26,105,106]. So, when Mannheimia haemolytica enters a BHV-1 infected lung, it encounters leukocytes whose recruitment and LFA-1 expression (and hence the leukotoxin susceptibility) are increased [26,106].…”
Section: Molecular Synergies With Other Pathogensmentioning
confidence: 99%
“…The pathophysiology of bovine pneumonic pasteurellosis is initiated by bacterial virulence factors and the host immune response [8,18,22,30]. During infection, Mannheimia haemolytica secretes a heatlabile leukotoxin, which stimulates polymorphonuclear neutrophilic leukocytes (PMN) to release the pro-inflammatory mediator leukotriene B 4 (LTB 4 ) and forms transmembrane pores in these cells, leading to cell death [18,34].…”
Section: Introductionmentioning
confidence: 99%
“…During infection, Mannheimia haemolytica secretes a heatlabile leukotoxin, which stimulates polymorphonuclear neutrophilic leukocytes (PMN) to release the pro-inflammatory mediator leukotriene B 4 (LTB 4 ) and forms transmembrane pores in these cells, leading to cell death [18,34]. This process is exacerbated by pro-inflammatory cytokines produced by the host [30]. The release of LTB 4 results in the recruitment of additional PMN to the lung.…”
Section: Introductionmentioning
confidence: 99%